The Influence of Different Media on The Physiological Response of Nila Fish (Oreochormis nilaticus) - M. Ali Akbar; Sri Jayanthi; Samsul Fajri; Khairunnisa; Arini Shinta Zahara; Muliani Tiana Sari; Mardiah (Jurnal Biologi Tropis, 2023)
Nila fish (Oreochromis niloticus) is one of the leading commodities in freshwater fish cultivation in Indonesia is a freshwater fish commonly found in Indonesian waters. Media will be the main obstacle in cultivating tilapia on idle land (land that cannot be operated). Different water media influence the physiological responses of tilapia fish. The purpose of this activity is to determine the effect of differences in freshwater, brackish water and sea water media on the physiological response of tilapia fish. The parameters of this research are differences in water media, physical factors of the media, survival of tilapia fish, respiration rate of tilapia fish, mobility of tilapia fish, weight of tilapia fish and flexibility of tilapia scales. This study used quantitative methods with a completely randomized design (RAL). The collection technique makes observations. Data were analyzed using ANOVA with a significance level of 5%. The results of this study show that differences in the aquatic environment significantly affect the physiological response of tilapia. Where in sea water the fish mortality rate is quite high compared to fresh water and brackish water.